PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES BAGI GURU MADRASAH ISLAMIAH (MI) MA’ARIF TINGKIR LOR - Setiyarini, Budi (Universitas Mataram, 2024)
Post-pandemic learning in madrasas requires adaptation so that it can be implemented in a blended manner. However, teachers still need assistance to develop online technology-based learning media. This service aims to train teachers to develop learning media based on Google Sites. The hope is that teachers' understanding and skills will increase. The method used in this service is PAR. This training activity included nine teachers at MI Maarif Tingkir Lor, Salatiga City. Technically, lecture and assignment methods are used to support training activities. Based on the training results, this service activity has achieved success, as seen from the results of self-evaluation (86%) and teacher satisfaction (85%) in participating in training activities achieved at a Very High level. Considering that in the initial survey, the teachers were only at the Low level (52%). Teachers can also create and display various assignments based on observations of the Google Sites-based learning media being developed. In the next service activity, training regarding learning media development can vary, not only online-based media but also offline, considering that learning can currently be in a blended mode.